The treatment efficacy of bone tissue engineering strategy for repairing segmental bone defects under diabetic condition - Wang, Xiangsheng; Xiang, Can; Huang, Chunhua; Cheng, Hanxiao; Zhou, Zhentao; Zhang, Jufang; Xie, Hui (Frontiers in Bioengineering and Biotechnology, 2024)
Background Diabetes mellitus is a systematic disease which exert detrimental effect on bone tissue. The repair and reconstruction of bone defects in diabetic patients still remain a major clinical challenge. This study aims to investigate the potential of bone tissue engineering approach to improve bone regeneration under diabetic condition. Methods In the present study, decalcified bone matrix (DBM) scaffolds were seeded with allogenic fetal bone marrow-derived mesenchymal stem cells (BMSCs) and cultured in osteogenic induction medium to fabricate BMSC/DBM constructs. Then the BMSC/DBM constructs were implanted in both subcutaneous pouches and large femoral bone defects in diabetic (BMSC/DBM in DM group) and non-diabetic rats (BMSC/DBM in non-DM group), cell-free DBM scaffolds were implanted in diabetic rats to serve as the control group (DBM in DM group). X-ray, micro-CT and histological analyses were carried out to evaluate the bone regenerative potential of BMSC/DBM constructs under diabetic condition. Results In the rat subcutaneous implantation model, quantitative micro-CT analysis demonstrated that BMSC/DBM in DM group showed impaired bone regeneration activity compared with the BMSC/DBM in non-DM group (bone volume: 46 ± 4.4 mm3 vs 58.9 ± 7.15 mm3, *p < 0.05). In the rat femoral defect model, X-ray examination demonstrated that bone union was delayed in BMSC/DBM in DM group compared with BMSC/DBM in non-DM group. However, quantitative micro-CT analysis showed that after 6 months of implantation, there was no significant difference in bone volume and bone density between the BMSC/DBM in DM group (199 ± 63 mm3 and 593 ± 65 mg HA/ccm) and the BMSC/DBM in non-DM group (211 ± 39 mm3 and 608 ± 53 mg HA/ccm). Our data suggested that BMSC/DBM constructs could repair large bone defects in diabetic rats, but with delayed healing process compared with non-diabetic rats. Conclusion Our study suggest that biomaterial sacffolds seeded with allogenic fetal BMSCs represent a promising strategy to induce and improve bone regeneration under diabetic condition.